Multiple integer packing for optimizing partial homomorphic encrypted databases - Sasidharan, Mythily A.; Pathari, Vinod (2016 International Conference on Advances in Computing, Communications and Informatics (ICACCI), 2016)
Database compromises are increasing nowadays, and database encryption is gaining its importance. Database encryption increases the size of the data, and time for processing the data. Optimizing the underlying encryption schemes helps to improve the performance of the encrypted databases. Processing queries over encrypted data, without decrypting it remained a holy grail until CryptDB. CryptDB is the first practical system which supports almost all queries over encrypted database. It leverages partial homomorphic encryption and SQL-Aware encryption scheme for encrypted query processing. CryptDB also suffers from storage and time issues. We propose packing of integers into a single field as a solution to reduce space issue of CryptDB. Any system which uses additive homomorphic schemes for encryption can adopt this method for storage optimization.